Marketing personalny jako instrument kształtowania elastyczności organizacji - Brol, Marian W.; Rzońca, Waldemar (Personal marketing as a tool of shaping flexibility of organization, 2006)
In the paper the stages of the development of an enterprise as well as the crisis situations accompanying these stages are presented. The decisive meaning of people in avoiding crises and their importance in the shaping of flexibility of an organization are indicated. As to human resources, the flexibility of the work potential is defined and personal marketing as a tool of shaping this flexibility is pointed out. Moreover the essence of personal marketing (PM) is discussed and the attention is paid to the variety of the interpretation of the notion of PM as well as to its close connection with the conception of Human Resource Management. Furthermore the aims of personal marketing are divided into systemic and operational, the comparison of chosen PM models is presented and the original marketing-mix vision for interior PM is suggested.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 73-81